Enfoque de derechos humanos en la política pública de discapacidad (2007)
The evolution of the concept of disability has moved from a biomedical focus to a human rightsfocus in the last years. The human rights focus regards people with disabilities’ individual features withrelation to their social, cultural y physical context. The interaction conditions between people and theircontext determines someone’s disability magnitude, as well as their family’s and the society’s disabilitymagnitude. This article will examine some issues object of debate among those who intent to build relationships between public policies, national and international development strategies and human rights international law. Besides, it will analyze some points of view about the pertinence of a human rights focus inColombia social, cultural and political context. The social, economic and cultural context and Colombian international commitments press on to make an effort to connect local and national policies, global tendencies of development and compliance with human rights and humanitarian law in order to achieve a more comprehensive vision. It will allowsociety to confront and solve disability problems in a better way.The Disability Intervention National Program has its grounds in the following conceptual elements:Risk Social Management (RSM), which refers to the economic theory that supports a social protection focus. This last focus is the creation base of the Social Protection Office.In the field of disability, the discussion’s main question is whether policies should be build from aRMS focus or from a civilian participation focus, which is more compatible with the approach previousthe Conpes document.